Investigation of High Current Tetracene-TFT Using Surface Nitrided SiO2 Gate Insulator Film. (18th August 2016) - Nakao, Hiroki; Hori, Kabuto; Iwazaki, Yoshitaka; Ueno, Tomo
Abstract : The use of surface nitrided SiO2 film as gate insulator of tetracene-TFT (Thin Film Transistor) has been proposed. Using Ar/N2 mixture gas plasma, the nitridation has been carried out on the SiO2 surface to remove charge-trapping sites due to hydroxyl groups. As a result, transistor output characteristics have been drastically improved with extremely high current level using tetracene film as organic semiconductor material. Also, to clarify the difference of the property of tetracene/SiO2 interface of each sample, C-V measurement has been carried out. After the nitridation have been done on the SiO2 surface that had been etched with dil-HF to make hydroxyl groups, the width of C-V hysteresis is decreased. Therefore we can conclude the surface nitridation of SiO2 films with Ar/N2 plasma are effective method to remove charge-trapping sites related to hydroxyl groups and improve transistor output characteristics.